Counterinsurgency Scorecard Update - Paul, Christopher; Clarke, Colin P. (RAND Corporation, 2023)
A key finding of previous RAND research on insurgencies worldwide since World War II was that an overall score on a scorecard of 15 equally weighted good and 11 equally weighted bad counterinsurgency factors and practices distinguished conflicts’ historical outcomes. Using the scorecard approach and an expert elicitation exercise, a RAND study sought to extend the findings to the case of Afghanistan in 2015.